2016
DOI: 10.15446/rev.colomb.quim.v45n3.61359
|View full text |Cite
|
Sign up to set email alerts
|

Comparación entre métodos de extracción para la obtención de volátiles a partir de pulpa de lulo (Solanum quitoense)

Abstract: Se compararon los métodos de extracción y destilación simultánea (SDE) y microextracción en fase sólida con espacio de cabeza (HS-SPME), acoplados a cromatografía de gases con detector de espectrometría de masas (GC-MS), para la recuperación de volátiles a partir de pulpa de lulo (Solanum quitoense). Se realizó un diseño completamente al azar aplicado al tipo de solvente para SDE/GC-MS, mientras que para HS-SPME/GC-MS se ejecutó un diseño a dos vías, teniendo como factores el tipo de fibra y la temperatura de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…These solvents, hexane, EB, and EA (slightly polar), share a common trait of being nonpolar. They are recognized for their ability to selectively extract nonpolar hydrocarbons. , It has been reported that SS contains a diverse range of both polar and nonpolar chemical compounds. The predominant composition of sludge consists of nonpolar compounds, aligning with the extraction yields observed with EB due to its nonpolar nature.…”
Section: Resultsmentioning
confidence: 99%
“…These solvents, hexane, EB, and EA (slightly polar), share a common trait of being nonpolar. They are recognized for their ability to selectively extract nonpolar hydrocarbons. , It has been reported that SS contains a diverse range of both polar and nonpolar chemical compounds. The predominant composition of sludge consists of nonpolar compounds, aligning with the extraction yields observed with EB due to its nonpolar nature.…”
Section: Resultsmentioning
confidence: 99%